The Chinese Mandarin version of the esophageal-atresia-quality-of-life questionnaires for children and adolescents : evaluation of linguistic and content validity - Siqi Li and Michaela Dellenmark-Blom and Yong Zhao and Yichao Gu and Shuangshuang Li and Shen Yang and Julia H. Quitmann and Jinshi Huang (International journal of environmental research and public health : IJERPH, 2022)
Background: After repair of esophageal atresia (EA), children risk digestive and respiratory morbidity, but knowledge of their health-related quality of life (HRQOL) in China is lacking. The EA-QOL questionnaires were developed in Sweden and Germany to evaluate condition-specific HRQOL in children with EA aged 2–7 and 8–17. This study aimed to evaluate the linguistic and content validity of the Chinese Mandarin version of the EA-QOL questionnaires. Methods: The procedure was conducted in compliance with international standards, including a forward-backward translation procedure, expert reviews, and cognitive debriefing interviews with 14 Chinese families of children with EA (parents of 8 children aged 2–7/6 children aged 8–17 and their parents). Results: Following forward-backward translation, minor issues were identified and solved. In interviews, all participants rated all EA-QOL items easy to understand, none expressed negative emotions about them and most described them comprehensive and relevant for EA. Leading from cognitive debriefing, three EA-QOL items in the questionnaire version for children aged 2–7 and three EA-QOL items in the questionnaire version for children aged 8–17 were modified in the Chinese language to improve cultural appropriateness and/or clarity. Conclusion: The Chinese Mandarin version of the EA-QOL questionnaires achieved satisfactory linguistic and content validity. This can help increase focus of HRQOL in research and clinical practice of children with EA in China.
Keywords: cognitive debriefing; content validity; cross-culturaltranslation; esophageal atresia; quality of life